Effect of Supra Choroid Triamcinolone Acetate On Intraocular Pressure: Supra Choroid Triamcinolone Acetate for Intraocular Pressure - Shah, Syed Sohail Ahmed; Haseeb, Uzma; Ahmed, Nasir; Ahmed, Israr; Ahmed, Shoaib; Shah, Shahid Hussain (Pakistan Journal of Health Sciences, 2025)
Intraocular pressure is a critical parameter in maintaining the physiological function of the eye. Dysregulation of Intraocular pressure can lead to ocular pathologies. Objective: To evaluate change in intraocular pressure after supra-choroidal triamcinolone acetonide use. Methods: This prospective interventional studyas carried out at the vitreo-retina Department of Al Ibrahim Eye Hospital Karachi, ISRA Postgraduate Institute of Ophthalmology for six months from July to December 2023. Adult patients attending the vitreoretinal Outpatient Department with resistant macular oedema were included. Intraocular pressure readings at 1 week, 4 weeks, 8 weeks and 12 weeks were recorded and compared with baseline values by applying One-way ANOVA keeping the p-value of <0.05 as statistically significant. Data were analyzed using SPSS v 22.0. Results: Among all, 21 (46.67%) cases received injections to the right eye and 24 (53.33%) cases to the left eye. The mean intraocular pressure before injection was 12.07 ± 2.14 mmHg. At three months’ post-injection, the mean intraocular pressure was 13.60 ± 5.2 mmHg. For the right eye; the mean pre-injection intraocular pressure was 12.38 ± 1.96 mmHg. Three months’ post-injection, the mean intraocular pressure was 13.43 ± 5.59 mmHg (p<0.001). For the left eye; the mean pre-injection intraocular pressure was 11.79 ± 2.28 mmHg while three months’ post-injection, the mean intraocular pressure was 13.75 mmHg ± 4.96 (p-0.06). Conclusions: It was concluded that supra-choroidal triamcinolone injections increase intraocular pressure but stabilized over time. These findings support earlier trials and add to the evidence of this therapy’s efficacy and safety.